(3SQGL GdYGHOjf aj TQM GdCQHYjfs - (3GdcQOj, ESeGYjd Hf eMehO Hf eMeO, J (B775 (3g`s ((3ChQL Hf eUWais)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj gOGfG dcJGHg haVdfG Ydi SGFQ GdCee hHYO bGd GdTjN QTjO GdOjf ESeGYjd Hf eMehO Hf eMeO GdcQOj (B( (3cPG (B) (3hGdO GdTjN TeS GdCFeI hUOQ GdCeI bO LeY CQHYjf MOjKG ef cJGH eTGQb GdCfhGQ GdfHhjI JCdja GdTjN MSf Hf eMeO Hf GdMSf GdUfYGfj hSejJg HSQGL GdYGHOjf aj TQM GdCQHYjfs
(3BNQgG (B:s
(3Ke Ef LejY eG ChQOJ aj gPG GdcJGH efbhd Yf MOGjb GdCRgGQ hYf TQYI GdESdGe ddEeGe GdYGde Rjf GdESdGe eMeO Hf CHj HcQ GdeZJQ (B( (3cPG (B) (3hYf GdeNJGQ ef efGbH GdCNjGQ ddTjN eLO GdOjf CHj GdSYGOGJ eHGQc Hf eMeO GdLRQj SbGge Gddg JYGdi HGdQMeI hGdZaQGf (B( (3cPG (B) (3hCScfge HMGHM GdLfGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1 / 380s
(3EjVGM Gdecfhf (B2 / 7s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs